2013
DOI: 10.1161/strokeaha.112.677617
|View full text |Cite|
|
Sign up to set email alerts
|

Ischemic Preconditioning Reduces Neurovascular Damage After Hypoxia-Ischemia Via the Cellular Inhibitor of Apoptosis 1 in Neonatal Brain

Abstract: Results-IP reduced apoptosis, selectively increased cIAP1 in neurons and vascular endothelial cells, and provided long-term neuroprotection against HI. Intracerebroventricular delivery of cIAP1 small interfering RNA significantly attenuated IPmediated cIAP1 upregulation and neuroprotection in vivo. In vitro, OGD preconditioning induced cIAP1 and protected against OGD cell death in SH-SY5Y neuronal and human microvascular endothelial cells-1. Knockdown of cIAP1 by lentivirusmediated short hairpin RNA decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…While the underlying mechanism leading to BBB damage was shown to involve induction of apoptosis in endothelial cells, the application of antiapoptotic agents resulted in a reduction of the endothelial permeability. 38 Therefore, we propose that ischemia-related BBB breakdown is predominantly driven by structural alterations affecting the endothelial integrity. In the context of potentially deleterious events originating from abrupt reopening of cerebral vessels (reperfusion injury), it is important to note that we observed differences neither in regard to expression patterns of essential junctional proteins such as occludin, claudin 3, claudin 5, ZO 1, or VE-cadherin, nor in regard to ultrastructural alterations in the endothelial layer between permanent and transient ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…While the underlying mechanism leading to BBB damage was shown to involve induction of apoptosis in endothelial cells, the application of antiapoptotic agents resulted in a reduction of the endothelial permeability. 38 Therefore, we propose that ischemia-related BBB breakdown is predominantly driven by structural alterations affecting the endothelial integrity. In the context of potentially deleterious events originating from abrupt reopening of cerebral vessels (reperfusion injury), it is important to note that we observed differences neither in regard to expression patterns of essential junctional proteins such as occludin, claudin 3, claudin 5, ZO 1, or VE-cadherin, nor in regard to ultrastructural alterations in the endothelial layer between permanent and transient ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…After 1 hour, the pups were placed in airtight 500-mL containers with 8% oxygen flow rate of 3 L per minute for 2 hours. [6][7][8]10 The pups were randomly assigned into different groups: intraperitoneally injected with 7-nitroindazole (7-NI; 75 mg/kg), a nNOS inhibitor; aminoguanidine (AG; 300 mg/kg, in saline), an inducible NOS (iNOS) inhibitor; or vehicle at 30 minutes before or 3 hours after HI. Technicians performed the experiments, while investigators masked to the groupings did the quantitative measurements.…”
Section: Hypoxic Ischemia Injurymentioning
confidence: 99%
“…The percentage of cortical area loss in the lesion versus the non-lesion hemisphere was determined. [6][7][8]10 NOS Activity…”
Section: Brain Damage Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Both animal and clinical studies have shown damage to the blood-brain barrier following neonatal HI, further indicating that these insults are associated with vascular damage (Kumar et al, 2008;Muramutsi et al, 1997). Furthermore, tissue plasminogen activator induces vascular production of gelatinases (MMP-2 and MMP-9) after neonatal HI, which aggravates brain injury (Omouendze et al, 2013;Svedin et al, 2007) and several studies in the immature brain show that vascular effects are critical for the development of tolerance to injury (Gustavsson et al, 2007;Lin et al, 2010Lin et al, , 2013. For example, we found that hypoxic preconditioning upregulated multiple vascular genes, enhanced angiogenesis and attenuated the decrease in cerebral blood flow during the subsequent HI (Lin et al, 2010).…”
mentioning
confidence: 54%